Strategic moves [compact disc, unabridged] - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2011)
While enjoying dinner at Elaine's, attorney Stone Barrington is shocked when his boss arrives unannounced and hands him a check worth one million dollars. The money is from Stone's new client, who is connected to Stone's undercover dealing with the British MI6. But just as he accepts the case, he learns that his client might be behind an elaborate Ponzi scheme, the magnitude of which could destroy even Stone's decorated career.